A comprehensive thermodynamic analysis of an integrated solar enhanced oil recovery system for applications in heavy oil fields - Abdul Salam Abd (14151648) (2022)
In this work, we present an integrated energy system for solar enhanced oil recovery (SEOR) process accompanied with electricity generation, fresh water and elemental sulfur production. The system shows the possibilities of integrating solar energy in upstream and downstream oil industry applications while offering the same quality of service. Such studies are of great interest to the Gulf Cooperation Council (GCC) region where solar irradiance is high during the year and where an abundance of mature heavy oil reservoir is present. We harness the solar energy from the sun to produce high quality steam at elevated temperature by the means of concentrated solar power technology through solar towers. The steam is used in generating electricity that is used for artificial lift purpose in the production wells, and provides steam suitable for injection purposes in tertiary recovery phase for hydrocarbon reservoirs. The overall system is analyzed in terms of energy and exergy efficiencies and the effects of different operating system parameters are evaluated. The steam generator and the furnace have the highest exergy destruction rates at a relative percentage of 41.3% and 39%. The energy and exergy efficiencies for the Claus process is reported at 78.2% and 18.2%, while the energy and exergy efficiencies of the overall system are calculated as 84% and 33.7%, respectively. Assuming that around 16% of the oil in place in the analyzed reservoir is accessible through Huff n’ Puff, then 3, 822, 250 kg of oil is produced while injecting 67, 500 kg of steam of density 0.54 kg/bbl at reservoir conditions. Other Information Published in: Energy Conversion and Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.enconman.2021.115161